Расчет соленоидов с программируемым магнитным полем для фокусировки и ускорения заряженных частиц - Бутенко, В.И.; Иванов, Б.И. (Вопросы атомной науки и техники, 2000)
Создание внешних неоднородных магнитных полей заданной конфигурации относится к классу некорректно поставленных задач в том смысле, что в пределах заданной точности они не имеют однозначного решения. В данной работе задача решается, с применением метода регуляризации А.Н. Тихонова, для соленоидов, состоящих из секций прямоугольного сечения, а искомыми параметрами являются толщина намотки, длина секции, координаты секций. Критерием оптимизации является минимум нормы решения. Приведены примеры расчета соленоидов для создания неоднородных магнитных полей в модели двухпучкового электронно-ионного ускорителя и в адиабатической плазменной линзе Морозова для фокусировки ионных пучков. For many problems of forming, acceleration and focusing
of the charged particles it is necessary to create external
non-uniform magnetic fields with specific configuration
and within the framework of given accuracy. In
accordance with the work of Tikhonov A.N. and Arsenin
V.Ya. (Methods of the Incorrect Problems Solving, M.:
Nauka, 1986. 288 p.), this problem is incorrect inverse
one (i.e., ill-posed) because it have no single-valued
solution within the framework of given accuracy.
Accordingly to the regularization method of A.N.
Tikhonov, from the set of possible solutions the wanted
one is chosen that optimized on specific criterion. In this
work the magnetic fields is created with the help of the
section solenoids consisting of coaxial placed sections.
Magnetic field intensity created by the each section
depends non-linearly on sections parameters. Such
parameters are, for example, geometrical sizes of the
sections, their mutual placement (sections coordinates),
current density. The problem is solved for the case of
rectangular cross-section and parameters being found are
winding thickness, section length, sections coordinates.
Optimization criterion is the minimum of the solution
norm. Specific examples of solenoid calculation is
presented for creation of non-uniform magnetic fields for
some variants of adiabatic plasma devices for focusing of
ion beams, and for a model of the two-beam electron-ion
accelerator.